RELATIONSHIP OF JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT TO TURNOVER INTENTION IN PT.MEGA KAPUAS MULTINIAGA EMPLOYEES IN JAKARTA - Michael Candra Jaya; I Putu Artaya (NAROTAMA UNIVERSITY, Indonesia, 2020)
This study aims to determine the relationship between job satisfaction and organizational commitment to the turnover intention of employees of PT. Megakapuas Multiniaga in Jakarta. This study uses a quantitative approach. The population in this study were employees of PT. Megakapuas Multiniaga in Jakarta. The sample used is 100 respondents using a questionnaire that is distributed directly to the respondents. Meanwhile, the analysis technique used is to use the correlation method in two ways, namely the calculation of the formula and SPSS 16.0. The results of the questionnaire data calculation state that the independent variables, namely job satisfaction (X1) and organizational commitment (X2), have a positive and insignificant relationship to turnover intention. The test of the men instrument in this study used the validity test, reliability test, correlation test using the calculation formula, and using the Spearman rank correlation test. The results showed that there was an influence between job satisfaction and organizational commitment on turnover intention. Based on the results of testing the variable job satisfaction to turnover intention, the value of r count is 0.058 with a significance of 0.578> 0.05 and organizational commitment to turnover intention, it is known that the value of r-count is 0.049 with a significance of 0.487> 0.05. In this study, there are 2 hypotheses. The first hypothesis states that job satisfaction has a positive and insignificant relationship with turnover intention and the second hypothesis states that organizational commitment has a positive and insignificant relationship with turnover intention.